Electoral bias and policy choice: Theory and evidence - Timothy Besley; Ian Preston (Institute for Fiscal Studies (IFS), 2006)
This paper develops a new approach to studying how electoral bias in favor of one party due to the pattern of districting aects policy choice. We tie a commonly used measure of bias to the theory of party compe- tition and show how this aects policy choice. The usefulness of the approach is illustrated using data on local government in England. The results suggest that reducing electoral bias leads parties to moderate their policies.
Keywords: 330; Wahlverhalten; Parteiprogramm; Großbritannien; Meinung; Politische Willensbildung; Ökonometrisches Modell